Design of a Web-Mobile Based Information System for Monitoring Maintenance and Repair Reports of Electrical Substations - Leni, Leni; Wibowo, Adi (Institut Teknologi Bisnis AAS Indonesia, 2025)
The manual workflow for reporting maintenance and repair of electrical substations at PT Haleyora Power, which relies on WhatsApp and Microsoft Excel, creates various obstacles, such as delays, risk of data errors, and a minimal capacity for real-time monitoring. This research aims to design and implement a web-based monitoring information system to overcome these inefficiencies. The development method used is Prototyping, which emphasizes active user involvement through an iterative evaluation cycle. The system was built using PHP-MySQL and comprehensively tested based on five quality aspects from the ISO/IEC 25010 standard: functional suitability, reliability, usability, performance efficiency, and security. The research results show the system was successfully built and passed all tests, achieving 100% in functional suitability, high reliability with no data loss, and a usability score of 86%, which is categorized as 'very feasible' by users. The implemented system successfully transformed the manual reporting process into a centralized digital workflow, significantly improving efficiency, data accuracy, and providing real-time monitoring capabilities for management.